Simulation And Experimentation Of Water Hydraulics Technology For Automatic Traditional Cookies Production - Yusof, Ahmad Anas; Misha, Suhaimi; Md Isa, Mohamed Hafiz; Wasbari, Faizil; Ibrahim, Mohd Qadafie; Kasim, Mohd Shahir (Penerbit Akademia Baru, 2018)
This study proposes a low-cost water hydraulics food processor for a traditional cookies production. The objective of this project is to introduce the design and the working principle of the water hydraulics-driven food processor, and to simulate production process performances and capabilities. The basic design is similar to that of a traditional food processor. It consists of an electrical motor, an inverter, a triplex pump, two directional control valves and cylinders. Simulation software is used to design and simulate the movement of the machine. Electro-mechanical relays and timers are used in the machine development, to balance the requirement for a low cost and modern machine automation. PLC is used in the testing of the machine. Water is used as the pressure medium for the system. Cartesian robotics movement is applied for the system, with one cylinder controlling the batches of the cookies, and the other handling the cookies extrusion system. The system is simulated with respective flow and pressure.